Alcohol Consumption and Pancreatitis Mortality in Russia - Razvodovsky, Yury E (JOP. Journal of the Pancreas, 2014)
Context Pancreatitis is a major public health problem with high associated economic costs. The incidence of pancreatitis has increased in many European countries in recent decade. Accumulated research and empirical evidence suggests that excessive alcohol consumption is a major risk factor for both acute and chronic pancreatitis. Objective The aim of this study was to examine the aggregate-level relation between the alcohol consumption and pancreatitis mortality rates in Russia. Method Age-standardized sex-specific male and female pancreatitis mortality data for the period 1970-2005 and data on overall alcohol consumption were analyzed by means ARIMA (autoregressive integrated moving average) time series analysis. Alcohol consumption was significantly associated with both male and female pancreatitis mortality rates: a 1 liter increase in overall alcohol consumption would result in a 7.0% increase in the male pancreatitis mortality rate and in 2.3% increase in the female mortality rate. The results of the analysis suggest that 63.1% of all male pancreatitis deaths and 26.8% female deaths in Russia could be attributed to alcohol. Conclusions The outcomes of this study provide indirect support for the hypothesis that unfavorable mixture of higher overall level of alcohol consumption and binge drinking pattern is an important contributor to the pancreatitis mortality rate in Russian Federation. Image: Trends in male pancreatitis mortality rate and alcohol consumption.